2019
DOI: 10.1088/2631-8695/ab58d9
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Experimental investigation of dry turning of AISI 1040 steel with TiN coated insert

Abstract: Quality and productivity plays a pivotal part in the current manufacturing scenario. The current investigations are expected to evaluate the superlative handle environment which may fulfill the prerequisites of both quality as well as productivity. This work is centered on numerical modeling along with optimization model based on Box Behnken design strategy to optimize the machining parameters such as spindle speed, feed , depth of cut and nose radius on the reaction characteristics specifically, surface rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Material. In this research, a commercial and commonly used AISI 1040 steel [26,30,37], whose chemical composition and mechanical properties are shown in Table 1, was used.…”
Section: Experimental Setup For Machiningmentioning
confidence: 99%
See 2 more Smart Citations
“…Material. In this research, a commercial and commonly used AISI 1040 steel [26,30,37], whose chemical composition and mechanical properties are shown in Table 1, was used.…”
Section: Experimental Setup For Machiningmentioning
confidence: 99%
“…e study of Haque et al [27] found that feed rate, depth of cut, and cutting condition with water are the most significant factors affecting the surface roughness for turning of AISI 1040 steel. Prakash and Krishnaiah [28], Pavani et al [29], and Nair et al [30] studied the effect of cutting speed, feed rate, and depth of cut on surface roughness for turning of AISI 1040 steel. However, Nair et al [30] suggested the same three factors to study the effect of tool vibration on flank wear and surface roughness during high-speed machining of 1040 steel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst different grades of steel, AISI 1040 steel has wide usage in the manufacturing sector and has hence received widespread attention of researchers [8][9][10][11][12]. AISI 1040 steel has usage in production of studs, springs, rods, different types of bolts, couplings and crankshafts [3].…”
Section: Introductionmentioning
confidence: 99%
“…A significant effort has been made to improve the quality characteristics of machined AISI 1040 steel using suitable machining parameters, use of lubricants, cryogenic cooling, etc [2,[13][14][15][16]. The parameters that were considered are speed, feed rate, depth of cut, tool material, work-piece hardness, minimum quantity lubricant (MQL), etc [7][8][9][10][11][12][13][14][15][16]. The responses or the quality parameters include surface roughness, fractal dimension, multiple roughness characteristics, tool wear and cutting forces [7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%